X-Slotted circularly polarized antenna with parasitic patches - T P Madhav, B; Khan, Habibulla; Sri Harsha, B; Sai Kumar, P; Lavanya, M; Veena, K; Venkateshwara Rao, M (International Journal of Engineering and Technology, 2017)
A compact circularly polarized antenna having x-slot in the parasitic patches have been proposed in this article. Four driven patches which are capacitively loaded with the help of the feeding loop and four parasitic patches which generate circular polarization because of the sequentially rotated structures are noticed in the proposed modal. With combination of the CP mode with the feeding loop we can observe the broadened axial ratio bandwidth. Comparative analysis has been observed for each side facing driven elements and side and edge facing parasitic elements with X-slot have been observed. The proposed antenna works at the bands of 5.04-5.83GHz and 6.34-6. 81GHz which works for WLAN application. The proposed modal and its iterations have been analyzed using ANSYS EM Software. The results show an enhanced impedance bandwidth of 22 percent and axial ratio bandwidth of over 15percent has been noticed in the proposed modal. A constant gain has been noticed all over the analyzed modals.
Keywords: Circular polarization (CP); Sequential phase; Parasitic patches; WLAN